A Study on Women’s Perceptions of Intimate Partner Violence in Egypt - Khodary, Yasmin; Kamel, Nour (CV. Era Digital Nusantara, 2023)
The purpose of this study is to investigate women’s perceptions of the main reasons behind their exposure to intimate partner violence (IPV) in Egypt. An online survey was conducted with a random sample of 277 respondents from Cairo and in-depth semi-structured interviews with 20 women who have been subjected to IPV in addition to observation to their living conditions. According to the conversations with the interviewees, the prevalence of IPV can be explained as a means of discharge from their structural conditions and stress factors. Around 79% of the respondents relate IPV with poverty, 65% relate it with lack of economic resources, and 90% believe that education is a triggering factor for it. Only 14% are decisive in associating IPV with a certain social class. The research finds that adverse structural conditions in poor communities such as poor housing, lack of water delivery, lack of education, lack of stable income and the lack of any social or economic opportunities explains the high rate of IPV among poor people. Men’s image of themselves and their manhood is severely threatened. Such a psychological status translates into feelings of depression, anxiety, frustration, anger, and fury leading to IPV. While IPV may be pervasive, is not inevitable. Both government and civil society have a key role in reducing the risk factors and addressing the reasons behind violence against women.